The Relationship Between Website-Based Interactive Indonesian Language Learning Media and Students’ Cultural Literacy - Manalu, Emilia; Jesiska Purba, Natalia; Angelia Purba, Nancy (Jurnal Komunitas Bahasa, 2025)
This study aims to examine the relationship between the use of interactive website-based Indonesian language learning media and students’ cultural literacy. The research is grounded in the need for Indonesian language learning to strengthen not only linguistic competence but also cultural understanding in the digital era. A quantitative approach with a correlational design was employed. The population consisted of 150 students at Universitas HKBP Nommensen Pematangsiantar, and a sample of 100 students was selected using proportional random sampling. Data were collected through a Likert-scale questionnaire containing 20 items for interactive media use and 20 items for cultural literacy, supported by observations of students’ learning activities. Data analysis was conducted using Pearson correlation to determine the relationship between variables and simple linear regression to assess the magnitude of influence. The results indicate that the use of interactive website-based learning media is in the high category, while students’ cultural literacy is in the medium–high category. Pearson’s analysis shows a positive and significant relationship between the two variables (r = 0.635; p < 0.05). Regression analysis further reveals that interactive media contributes 40.3% to the variance in cultural literacy. These findings demonstrate that website-based interactive learning media are effective in supporting the enhancement of students’ cultural literacy in higher education.